Lasting effects of cognitive emotion regulation: neural correlates of reinterpretation and distancing - Hermann, Andrea (Soc Cogn Affect Neurosci, 2020)
Reinterpretation and distancing are two cognitive reappraisal tactics, used to regulate one’s emotions in response to emotion-eliciting stimuli or situations. Relatively less is known about their (differential) lasting effects on emotional responding and related neural correlates. This functional magnetic resonance imaging study investigated 85 healthy females, participating in a 2-day cognitive emotion regulation experiment. On the first day, participants were instructed to passively look at, reinterpret or distance from repeatedly presented aversive pictures. One week later, they were re-exposed to the same stimuli without regulation instruction, in order to assess lasting effects. The main outcome measures comprised ratings of negative feelings and blood-oxygen-level-dependent responses. Lasting effects for reinterpretation compared with looking at aversive pictures during passive re-exposure 1 week later were reflected in stronger activation of the left amygdala, the ventromedial prefrontal cortex (vmPFC) and reduced negative feelings. Neither distancing compared with looking at aversive pictures nor reinterpretation compared with distancing did result in significant effects during re-exposure. These findings indicate that reinterpretation leads to reduced negative feelings 1 week later, which might be mediated by inhibitory vmPFC activation or stronger positive emotions during re-exposure. However, the missing difference compared with distancing questions the specificity of the results and the mechanisms underlying these two cognitive reappraisal tactics.